Relationship Between in situ Conserved Wild Wheat Species, Associated Plants and Soil Characteristics - Alptekin Karagöz; Çetin Arcak; İbrahim Hakkı Güçdemir (Journal of Agricultural Sciences)
A comprehensive knowledge of the ecology and associating plant species of wheat progenitors is important for plant scientists. This study was designed as a case study to focus on the relation between 5 wild relatives of wheat Aegilops spp. L. and Triticum spp. L. , their associated soil types and environmental and external variables in the Ceylanpınar State Farm of Şanlıurfa Province. The aim of the study was to explain the major physical factors affecting the existence of target species in the area. The following wild wheat species, which are all related with evalution of modern wheat were taken into consideration: Aegilops speltoides Tausch var. speltoides goat grass , Aegilops speltoides Tausch var. ligustica Savign. Fiori goat grass , Aegilops tauschii Coss. var. meyeri Griseb. ex Ledeb. Tausch's goat grass , Triticum monococcum L. ssp. aegilopoides Link Thell. einkorn and Triticum turgidum L. ssp. dicoccoides Körn. ex Asch.& Graebn. emmer . Association was observed between the target species, Poaceae species and herbaceous plants, while no association was noticed with perennial plants. Strong association was observed between rockiness and emmer. Einkorn was associated with slightly stoniness and slight grazing while Ae. speltoides ligustica was related with very stony areas and excessive grazing